Surface Redox Pseudocapacitance Boosting Vanadium Nitride for High‐Power and Ultra‐Stable Potassium‐Ion Capacitors. (10th July 2022) - Xu, Chengrong; Mu, Jinglin; Zhou, Tong; Tian, Shuang; Gao, Peibo; Yin, Guangchao; Zhou, Jin; Li, Feng
Abstract: Developing a high‐rate and stable battery‐type anode to match the capacitor‐type cathode is a critical issue for potassium ion capacitors (PICs). Surface‐redox pseudocapacitive materials can meet this demand due to their fast surface Faradaic reaction kinetics and superior structure stability during charging–discharging. Herein, a free‐standing anode by growing VN particle‐composed nanosheets on carbon fibers (VN@CFs) is developed. The VN@CFs is endowed with high reversible capacity of 245.8 mA h g –1 at 0.05 A g –1, high rate performance of 102.7 mA h g –1 at 6.0 A g –1, and long‐term stability. Based on the in situ XRD, ex situ XPS and TEM characterizations, and density functional theory calculations, it is proved that the potassium storage of VN derives from a surface‐redox pseudocapacitive mechanism between VN and K +, rather than an intercalation or conversion reaction. As expected, the as‐assembled PICs based on the VN@CFs anode show an ultrahigh power output of 10.9 kW kg –1 when keeping an energy density of 49.2 Wh kg –1 and excellent capacity retention of 86.8% after 15000 cycles. Abstract : A free‐standing anode made by growing VN particle‐composed nanosheets on carbon fibers is developed for high‐power and stable potassium‐ion capacitors (PICs). Experimental analysis and theoretical simulations reveal the surface‐related redox pseudocapacitive mechanism of VN. The derived PICs exhibits superior rate capability and remarkable long‐term stability.